Association of serum lactate dehydrogenase, creatinine kinase and adiposity with basal lactate concentration in male and female jamaican athletes - Facey, A.; Dilworth, L.; Wright-Pascoe, R.; Irving, R. (International Journal of Sports Science, 2017)
Research has shown that basal lactate increases with body fat in males of West Indian descent. The relationship in females of West Indian descent has however not been clearly elucidated. Lactate Dehydrogenase (LDH) and creatinine (CK) are associated with energy metabolism and are involved in fat storage. Since basal lactate increases with adiposity, these enzymes may impact the regulation of basal lactate more significantly than fat. The study seeks to establish the relationship between adiposity and fasting or resting serum lactate (basal lactate) in male and female athletes and to ascertain if the concentrations of these enzymes contribute to the level of basal lactate. In this study of 23 male and 10 female athletes and 19 males and 17 female non-athletes, fasting or resting basal lactate, body fat percentage and concentration of CK and LDH were evaluated. Basal lactate was determined using a handheld lactate analyser and body fat percentage was determined using ultrasound technology. The concentration of the enzymes CK and LDH were also measured from serum. Results revealed that lactate increases with fat level in males and female`s athletes and non-athletes. Fat > 29% did not contribute to increased serum basal lactate concentration in females. Basal lactate concentration was not significantly impacted by the concentrations of CK and LDH. Body fat can be used to estimate basal lactate concentration in blood in male and female athletes. A post exercise assessment of serum CK and LDH and impact on basal lactate is warranted.